A multiwavelength study of spiral structure in galaxies. I. General characteristics in the optical. Issue 1 (28th January 2020) - Savchenko, Sergey; Marchuk, Alexander; Mosenkov, Aleksandr; Grishunin, Konstantin
ABSTRACT: Different spiral generation mechanisms are expected to produce different morphological and kinematic features. In this first paper in a series, we carefully study the parameters of spiral structure in 155 face-on spiral galaxies, selected from the Sloan Digital Sky Survey, in the three gri bands. We use a method for deriving a set of parameters of spiral structure, such as the width of the spiral arms, their fraction to the total galaxy luminosity, and their colour, which have not been properly studied before. Our method is based on an analysis of a set of photometric cuts perpendicular to the direction of a spiral arm. Based on the results of our study, we compare the main three classes of spirals: grand design, multi-armed, and flocculent. We conclude that: (i) for the vast majority of galaxies (86 per cent), we observe an increase of their arm width with Galactocentric distance; (ii) more luminous spirals in grand design galaxies exhibit smaller variations of the pitch angle with radius than those in less luminous grand design spirals; (iii) grand design galaxies show less difference between the pitch angles of individual arms than multi-armed galaxies. Apart from these distinctive features, all three spiral classes do not differ significantly by their pitch angle, arm width, width asymmetry, and environment. Wavelength dependence is found only for the arm fraction. Therefore, observationally we find no strong difference (except for the view and number of arms) between grand design, multi-armed, and flocculent spirals in the sample galaxies.